Genetic diversity in the Lusitano horse breed assessed by pedigree analysis - Vicente, António (2012)
Genetic diversity and population structure were analyzed in the Lusitano horse breed based on pedigree information of animals registered in the Studbook, to identify factors which may have affected the genetic variability of the breed, and provide the bases for the establishment of sustainable utilization programs. Pedigree records collected from 1824 to 2009, including information on 53,411 animals, were used in the analyses. The mean generation interval was 11.33±5.23 and 9.71±4.48 years for sires and dams, respectively, while the mean number of offspring registered was 13.13±22.53 for stallions and 4.00±3.38 for mares. All great-grandparents were known for the animals in the reference population (registered foals born from 2005 to 2009, n=9712), which had a mean number of equivalent generations known of 11.20±0.71 and an average inbreeding of 11.34±7.48%. For this population, the rate of inbreeding per year was 0.173±0.070, and the effective population size computed from this rate was about 28. The mean relationship among animals from the same and from different studs was 0.31±0.16 and 0.15±0.10, respectively. In spite of the high within-stud relationship, inbreeding has been kept lower than expected due to restrictions imposed by breeders on selection and allocation of mates. The effective number of founders, ancestors and studs contributing to the current genetic pool was 27.5, 11.7 and 5.4, respectively. Over the last 30 years, contributions to the genetic pool of Lusitano have been decreasing, with a reduction to about one-half in the effective number of founders and ancestors. Of the 267 founder sires, only 9 Y-chromosome sources are currently represented, with an effective number of 2.23. The diversity of mt-DNA sources is broader, with 129 lineages represented and an effective number of 42.8. The results of our study reflect the intensive emphasis that has been placed on a few sire-families over the years, and raise concerns regarding the conservation of genetic diversity for the future. Methods designed to minimize inbreeding and maximize the maintenance of genetic contributions from different founders and ancestors should be envisaged, to prevent further losses of genetic variability in the Lusitano horse breed.